LGBTQ Youths' School Athletic Experiences: A 40-Year Content Analysis in Nine Flagship Journals. Issue Volume 11:Issues 3(2017) (3rd July 2017) - Greenspan, Scott B.; Griffith, Catherine; Murtagh, Erin F.
ABSTRACT: The majority of youth identifying as lesbian, gay, bisexual, transgender, and queer (LGBTQ) experience harassment in school athletics, which increases the risks of mental health concerns and less physical activity involvement. The authors conducted a systematic content analysis of nine flagship journals to assess the representation of this critical issue within the scholarly literature. Results demonstrate a dearth of academic research within flagship journals, which may deter appropriate school-based initiatives and interventions. Implications for counseling and directions for future research are discussed.